Human Endometrial Regenerative Cells Attenuate Bleomycin-Induced Pulmonary Fibrosis in Mice - Yiming Zhao; Xu Lan; Yong Wang; Xiaoxi Xu; Shanzheng Lu; Xiang Li; Baoren Zhang; Ganggang Shi; Xiangying Gu; Caigan Du; Hao Wang (Stem Cells International)
Endometrial regenerative cells (ERCs) have been recently evaluated as an attractive novel type of stem cell therapy. Previous studies have demonstrated that most ERCs accumulated in the lung after injection and are successfully used to treat diseases such as cardiac fibrosis. However, relevant studies of ERCs in idiopathic pulmonary fibrosis (IPF) have not been reported. The present study was designed to examine the effects of ERCs on bleomycin-induced pulmonary fibrosis. All IPF models in C57BL/6 mice were induced by administrating 5 mg/kg bleomycin in PBS intratracheally. ERCs were isolated from healthy female menstrual blood and were injected (1 million/mouse, i.v.) 24 hours after induction. Wet/dry weight ratio assay, hydroxyproline content, pathological and immunohistological changes, MDA content, T-SOD activity, cytokine profiles, and RT-qPCR analysis were assessed 2 weeks after disease induction. The results showed that ERC treatment significantly decreased the wet/dry ratio and reduced collagen deposition. Histological analyses, Masson staining, and hydroxyproline content analysis indicated that ERCs could reduce collagen fiber production. Immunohistochemical staining revealed lower expression of TGF-β after ERC treatment. Furthermore, mice treated with ERCs had lower levels of IL-1β and TNF-α, but a higher level of IL-10 in both the lung and serum. Gene expression analysis demonstrated that ERCs potently suppressed the proapoptotic gene Bax, while increasing the antiapoptotic gene Bcl-2 and antifibrosis genes HGF and MMP-9. Our results indicate that human ERCs protected the lung from pulmonary fibrosis in mice through immunosuppressive and antifibrosis effects. Moreover, these findings formed a foundation for the further use of ERCs in clinical treatment.